Pengaruh Motivasi Kerja Dan Etos Kerja Terhadap Produktivitas Kerja Pada Pegawai Kantor Gubernur Provinsi Kalimantan Timur - ., Vina; Anitra , Vera; Hadiyanti , Sofia Ulfa Eka (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
The Governor's Office plays a strategic role as the central hub for coordination in regional decision-making and governance. Its core functions include public policy planning, oversight of government institutions, and the management of regional resources aimed at improving the quality of life and promoting sustainable local development. Employee performance within the Governor's Office is a key factor in the effective execution of these governmental duties.As such, attention to the productivity of civil servants (ASN) is essential, as productivity reflects how efficiently time, energy, and resources are used to achieve organizational goals (Sutrisno, 2023; Robbins & Judge, 2022).This study aims to examine the influence of work motivation and work ethic on employee productivity at the Leadership Administration Bureau of the East Kalimantan Provincial Governor's Office. A quantitative approach was applied using a survey method, with questionnaires distributed to 69 respondents. The data were analyzed using multiple linear regression.The results show that both work motivation and work ethic have a positive and significant impact on employee productivity, both individually and jointly. Together, these two factors account for 25.2% of the variance in productivity. These findings suggest that motivation and work ethic are critical in enhancing employee performance. Therefore, continuous efforts are needed to foster motivation and build a strong work ethic in order to achieve more effective and professional organizational performance.